Intestinal Uptake and Tolerance to Food Antigens - Xiong, Yuhong; Xu, Guifeng; Chen, Mingwu; Ma, Hongdi (Frontiers in Immunology, 2022)
Food allergy is a growing concern due to its increasing world-wide incidence. Strict avoidance of allergens is a passive treatment strategy. Since the mechanisms responsible for the occurrence and development of food allergy have not yet been fully elucidated, effective individualized treatment options are lacking. In this review, we summarize the pathways through which food antigens enter the intestine and review the proposed mechanisms describing how the intestine acquires and tolerates food antigens. When oral tolerance is not established, food allergy occurs. In addition, we also discuss the contribution of commensal bacteria of the gut in shaping tolerance to food antigens in the intestinal tract. Finally, we propose that elucidating the mechanisms of intestinal uptake and tolerance of food antigens will provide additional clues for potential treatment options for food allergy.